2020
DOI: 10.3390/ijerph17020651
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Oxidative Stress Status in Zebrafish (Danio rerio) Liver Induced by Three Typical Organic UV Filters (BP-4, PABA and PBSA)

Abstract: Organic UV filters are a kind of emerging pollutants, which have been widely used in personal care products (PCPs). This study evaluated the effects of benzophenone-4 (BP-4), 4-aminobenzoic acid (PABA), and 2-phenylbenzimidazole-5-sulfonic acid (PBSA) on the selected indices of antioxidative responses in zebrafish (Danio rerio) liver. Zebrafish were exposed to two different doses (i.e., 0.5 and 5 mg L−1) of semi-static water with three individual compounds. Liver samples were collected on 7 and 14 days to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 51 publications
(58 reference statements)
2
21
0
Order By: Relevance
“…These enzyme activities were found to be declined in the gills of fish when exposed to BP-3 at environmental concentration, which may be due to the inhibition of these enzymes by increased cellular H2O2 levels. This findings supported by Huang et al [21], reported that the activity of SOD and CAT in the liver of Zebra fish was inhibited by UV filters BP-4, PABA and PBSA exposure.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These enzyme activities were found to be declined in the gills of fish when exposed to BP-3 at environmental concentration, which may be due to the inhibition of these enzymes by increased cellular H2O2 levels. This findings supported by Huang et al [21], reported that the activity of SOD and CAT in the liver of Zebra fish was inhibited by UV filters BP-4, PABA and PBSA exposure.…”
Section: Discussionsupporting
confidence: 84%
“…These findings indicate that the accumulation of BP-3 in tissues may provoke ROS production, and in turn, affect the CAT activity, which catalyses and neutralizes the H2O2 H2O2 derived from oxidative stress. These findings were supported by Huang et al [21] who stated that UV filters BP-3 increased the LPO marker malondialdehyde in Zebra fish liver, which significantly changed during the whole BP-3 exposure period.…”
Section: Discussionsupporting
confidence: 73%
“…In fact, it shares a high level of genome structure with humans and, in detail, approximately 70% of human genes have at least one obvious zebrafish ortholog compared to 80% of human genes with mouse orthologs, thereby facilitating the use of zebrafish for understanding human genetic diseases [77,80]. This species is widely used to test the efficacy of some drugs [76,[81][82][83][84] and as an indicator organism for the study of the toxicological effects of different types of environmental pollutants (i.e., pesticides, industrial discharges, cosmetics; [85][86][87][88][89][90][91][92][93]. It is also an important model being inexpensive, low-maintenance and producing abundant offspring [94].…”
Section: Danio Rerio As a Model Organismmentioning
confidence: 99%
“…As mentioned earlier, the results shown by MDA were correlated to the results of stress indicators (SOD, catalase and glutathione). These stress indicators are the part of antioxidant defence system which are either enzymatic (SOD and catalase) or non-enzymatic (glutathione) and are frequently used to evaluate oxidative stress level in animals (Huang et al 2020). The enhanced level of HIF-1α protein indicates insufficient O 2 in cell that creates hypoxia and mediates the re-establishment of homeostasis in oxidatively stressed cell (Samenza 2005).…”
Section: Acidic Ph Affects Zebrafish Skeletal Musclementioning
confidence: 99%